2016
DOI: 10.1007/s10886-016-0768-x
|View full text |Cite
|
Sign up to set email alerts
|

Volatile Organic Compounds Emitted by Fungal Associates of Conifer Bark Beetles and their Potential in Bark Beetle Control

Abstract: Conifer bark beetles attack and kill mature spruce and pine trees, especially during hot and dry conditions. These beetles are closely associated with ophiostomatoid fungi of the Ascomycetes, including the genera Ophiostoma, Grosmannia, and Endoconidiophora, which enhance beetle success by improving nutrition and modifying their substrate, but also have negative impacts on beetles by attracting predators and parasites. A survey of the literature and our own data revealed that ophiostomatoid fungi emit a variet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
75
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(76 citation statements)
references
References 161 publications
(192 reference statements)
0
75
1
Order By: Relevance
“…Bacteria ( Acinetobacter spp., Pseudomonas aeruginosa ) ( 48 , 49 ), many yeasts ( 50 , 51 ), and the fungal tree pathogen Armillaria mellea ( 52 ) have also been proposed to use ethanol as a carbon source. In addition to detoxifying ethanol, ambrosia beetle fungal symbionts are known to produce ethanol, among other alcohols ( 53 and 54 ), which may maintain an alcohol-rich gallery environment even after its production by plant cells has ceased (i.e., because of tree death). Such consumption, production, and environmental accumulation of ethanol has been reported so far from only three lineages of yeasts, in which it has been shown to be a potent tactic for securing their food resource against other microbial and possibly also arthropod competitors ( 50 , 51 , 55 ).…”
Section: Discussionmentioning
confidence: 99%
“…Bacteria ( Acinetobacter spp., Pseudomonas aeruginosa ) ( 48 , 49 ), many yeasts ( 50 , 51 ), and the fungal tree pathogen Armillaria mellea ( 52 ) have also been proposed to use ethanol as a carbon source. In addition to detoxifying ethanol, ambrosia beetle fungal symbionts are known to produce ethanol, among other alcohols ( 53 and 54 ), which may maintain an alcohol-rich gallery environment even after its production by plant cells has ceased (i.e., because of tree death). Such consumption, production, and environmental accumulation of ethanol has been reported so far from only three lineages of yeasts, in which it has been shown to be a potent tactic for securing their food resource against other microbial and possibly also arthropod competitors ( 50 , 51 , 55 ).…”
Section: Discussionmentioning
confidence: 99%
“…The presence of enemies in the non‐indigenous lodgepole pine may be a result of most bark beetle enemies being generalists that utilize several bark beetle species reproducing in different tree species and, generally, they do not appear to rely on species‐specific host tree cues when locating bark beetle‐attacked trees. Instead, they may be attracted by bark beetle pheromones, host tree volatiles such as α‐pinene that are present in many tree species, or volatiles from host‐associated fungi (Kenis et al ., ; Kandasamy et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…Frontalin was tested since it has been shown that P. poligraphus responds to it. 1‐Hexanol was tested as it has been identified as a reppelent for other bark beetle species (Kandasamy, Gershenzon, & Hammerbacher, ). Since n ‐nonane was used as a solvent in the “wick‐bait” dispensers, it was also tested along with two potential alternatives, n ‐octane and n ‐decane.…”
Section: Methodsmentioning
confidence: 99%